2018
DOI: 10.1093/ecco-jcc/jjy014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcome of Early Combined Immunosuppression Versus Conventional Management in Newly Diagnosed Crohn’s Disease

Abstract: Top-down treatment did not result in increased clinical remission during long-term follow-up, compared to step-up treatment. However, lower relapse rates and a reduced use of anti-TNF agents and corticosteroids were observed. No difference was found in rates of endoscopic remission, hospitalization, surgery or new fistulas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 25 publications
3
42
0
Order By: Relevance
“…In adult patients, a lower hospitalization rate was observed during eight years (96 months) of follow-up (3). An endoscopic substudy of a Step-up/Topdown trial on 49 pediatric patients did not nd a difference in the time to the rst CD-related hospitalization (P = 0.67) (6), which is in line with our results. It has been shown in adult patients with CD that MH is linked to a lower risk of surgical resection (3).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In adult patients, a lower hospitalization rate was observed during eight years (96 months) of follow-up (3). An endoscopic substudy of a Step-up/Topdown trial on 49 pediatric patients did not nd a difference in the time to the rst CD-related hospitalization (P = 0.67) (6), which is in line with our results. It has been shown in adult patients with CD that MH is linked to a lower risk of surgical resection (3).…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown in adult patients with CD that MH is associated with a lower risk of surgical resection, lower hospitalization rate, decreased risk of relapse, and prolonged steroid-free remission (2)(3)(4)(5). However, some recent pediatric data indicate no bene t of MH on CD-related hospitalizations and surgery (6). More extensive pediatric data about MH and longterm outcome are still sparse.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that biologics are beneficial to growth (i.e., height and weight), especially in adolescent patients with CD [891314]. However, their effect on reducing the rate of surgical intervention remains debatable [151617]. Therefore, this study aimed to analyze the effects of biologics on growth and prognosis related to surgery in children and adolescents with CD.…”
Section: Introductionmentioning
confidence: 99%
“…This finding may be related to an inadequate statistical power resulting from the small number of patients with hospitalizations (≥3 times). Controversially, a retrospective study of 252 CD patients in Europe demonstrated that MH at 2 years after treatment was not associated with any unfavorable long-term outcome, including surgery, hospitalization, and a new fistula (24). Because unfavorable events might occur within 2 years, this result would have been more convincing if an accurate assessment of MH before adverse events was performed during follow-up.…”
Section: Discussionmentioning
confidence: 99%